2010
DOI: 10.2217/fvl.10.75
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Basis for Revaccination of HIV-Infected Children Receiving HAART

Abstract: With increasing access to antiretroviral therapy for children infected with HIV, especially in subSaharan Africa, better understanding of the development and maintenance of memory T-and Bcell responses to pathogens after immune reconstitution is needed to assess the risk of infection. Knowledge of long-term immune responses after starting HAART is of particular importance for policies on revaccination of HIV-infected children, who may lose protective immunity to prior infections and immunizations. We review no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 101 publications
2
16
1
Order By: Relevance
“…In the present study, depletion of SM B cells was observed in contrast to study by Jacobsen et al; this could be due to the younger age of children in the present cohort as SM cells generally accumulate with age. This preferential depletion of SM B cell pool emphasize the need to revaccinate HIV infected children receiving HAART as reported in previous studies …”
Section: Discussionsupporting
confidence: 76%
“…In the present study, depletion of SM B cells was observed in contrast to study by Jacobsen et al; this could be due to the younger age of children in the present cohort as SM cells generally accumulate with age. This preferential depletion of SM B cell pool emphasize the need to revaccinate HIV infected children receiving HAART as reported in previous studies …”
Section: Discussionsupporting
confidence: 76%
“…As in our study, other studies of measles revaccination in HIV-infected children on ART found that the response was related more to suppressed HIV replication than to CD4% 24,31 . This suggests that the ability to sustain an immune response to measles vaccination may be hindered by high levels of HIV replication, which is associated with turnover and depletion of B and T cells needed for memory 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of measles seropositivity after revaccination may involve a different immunological mechanism than measles seroconversion 23 , thus a separate analysis was performed to explore factors associated with seroconversion. We assessed the risk of measles seroconversion at 24 months post revaccination by log-binomial regression with robust error variance.…”
Section: Methodsmentioning
confidence: 99%
“…In healthy children younger than 10 years of age, the proportions of naïve T cells decrease as the immune system matures and encounters antigens, while memory T cell proportions increase. 5 Since control children were enrolled for only a single visit, our ability to differentiate between phenomena associated with aging, such as antigen exposure, and HAART duration was limited when comparing cellular subsets among HIV-infected children. We attempted to control for this by adjusting for age in statistical models and believe a large part of the considerable changes in T cell subsets can be attributed to HAART, as observed upon stratification of cell subset trajectories by age and sex.…”
Section: Discussionmentioning
confidence: 99%